Investigating Students’ Problems in Learning Speaking English at Mts Al-Kautsar School Pekanbaru - Febri Abshor; Andi Idayani (Yayasan Darussalam Bengkulu, 2026)
This study aims to identify the speaking barriers experienced by ninth-grade students at MTS Al-Kautsar School in Pekanbaru. A qualitative approach was employed, using observation and interviews to investigate the factors that hinder students' ability to speak English. The participants consisted of 20 ninth-grade students. The findings revealed nine major speaking barriers experienced by the students. The most prevalent barriers were the use of the native language and limited vocabulary, both reported by all participants. Other frequently identified barriers included difficulty expressing ideas spontaneously, shyness during debates and speeches, anxiety in formal speaking situations, and low participation in speaking activities. Additionally, fear of making mistakes, psychological barriers, and lack of self-confidence were reported by nearly half of the students. In contrast, lack of motivation to speak was found to be the least common barrier. Overall, the findings suggest that both affective factors, such as anxiety and self-confidence, and linguistic factors, such as vocabulary limitations, play a significant role in hindering students’ English-speaking performance.